INKLUSIFITAS BERAGAMA PEMBELAJARAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TEMA KEARIFAN LOKAL - Saputra, Eddy; Ali, Nur (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
The importance of creating an inclusive educational environment and promoting moderation in understanding religion is the focus of this research. This research discusses efforts to strengthen the profile of Pancasila students as an initiative to realize religious inclusivity and produce moderate Islamic students. The aim of this research is to explore the contribution of the Strengthening the Pancasila Student Profile Project to creating an inclusive educational environment and forming Islamic students who have a moderate understanding of religion. Qualitative research methods were used, with a case study approach as the analytical framework. Data was collected through observation, interviews, and document analysis related to the implementation of the project to strengthen the profile of Pancasila students. The research results show that this project is effective in stimulating moderate religious understanding among Islamic students. This project facilitates the integration of Pancasila values, which include aspects of tolerance, unity, and justice, supporting the formation of students' characters who can accept religious differences with an open attitude. Students' involvement in this project increases their understanding of plurality and stimulates positive interfaith dialogue. In this context, the project to strengthen the profile of Pancasila students is not only a means of religious learning but also a tool for forming inclusive and moderate attitudes towards differences in beliefs.